National Manpower Survey, 1973-1976 ([Verlag nicht ermittelbar], 1984)
This data collection contains information from a series of national surveys, conducted simultaneously across the criminal justice system, to ascertain national manpower strengths and goals, agency information and characteristics, and attitudes of the agency heads during the period 1973-1976. The National Manpower Survey was undertaken to assess the adequacy of existing federal, state, and local training and education programs meeting current personnel needs in various law enforcement and criminal justice functions and operations. The study intended to project future personnel and training needs, by occupation, in relation to anticipated availability of qualified personnel in order to assess the future adequacy of training and educational resources. It also sought to establish "needs priorities" as a basis for future training and academic assistance programs to be funded by the Bureau of Justice Statistics. The study design systematically covered the personnel needs in all state and local governmental agencies that were part of the law enforcement and criminal justice system. Sectors within the system included: (1) law enforcement, consisting of police departments and sheriff's agencies, ranging in size from one-person constabularies to large city departments employing 20,000 or more individuals, (2) corrections, including both adult and juvenile correctional institutions and agencies, and (3) the judicial process, including a wide range of courts with varying jurisdictions and scope, district attorneys or prosecutors' offices, and public defenders' offices. For this study, the Bureau of Social Science Research was responsible for the acquisition and assessment of existing statistical data as well as the design and execution of systematic mail surveys of agencies, officials, and employees within the law enforcement/criminal justice system. Nine nationwide surveys were directed to executives in criminal justice agencies, including chiefs of police (in both large and small departments), sheriffs (in both large and small departments), chief prosecutors, chief defenders, court administrators, wardens of adult correctional facilities, directors of juvenile correctional facilities, and chief probation and parole officers. Two additional surveys were sent to general and appellate jurisdiction courts. In the nine surveys directed to criminal justice executives, the instruments asked respondents for (1) an overall assessment of manpower problems, including personnel categories in which critical shortages might exist, and total personnel required to fulfill all agency duties and responsibilities, (2) desired and actual entry level standards, as well as entry level and in-service training content and requirements, (3) demographic, educational, training, and occupational background information about the executive respondent, (4) opinions about major obstacles to effectiveness and attitudes toward various issues such as team policing, plea bargaining, and computer-assisted case management, and (5) a fact sheet section dealing with agency employment by occupational category, salaries, and workloads. Each of the remaining two surveys was a census of general and appellate jurisdiction courts designed to yield basic statistical information regarding the courts and court systems' current staffing, training activities, and caseloads, and did not seek any attitudinal or subjective responses. Thus the agency itself was the reporting unit, with the respondent required only to be in a position to provide accurate, reliable information.